A dual signal model of pride displays in organizations. (2018) - Grandey, Alicia A.; Ferris, D. Lance; Melloy, Robert C.
Abstract: Pride is often felt in the work context, but should it be shown to others? Pride displays communicate one's own success and status, but can show a lack of interpersonal sensitivity. This double-edged nature of pride is not fully understood in organizational contexts; we do not know under what conditions pride displays are beneficial, or detrimental, to career advancement, team dynamics, and leader influence. In this article we integrate signaling theory with sensory habituation and sensitization concepts to develop a new contextualized model of pride at work. Specifically, we propose that pride displays are signals for two primary social judgments that have important implications for organizations: competence and warmth. We make the case that, while pride display under conditions of information asymmetry (lack of information about the sender) signals competence, repeated displays hasten habituation to that signal and instead foster sensitization to a (low) interpersonal warmth signal. Furthermore, additional characteristics of the sender, receiver and audience determine the signaling of these two social judgments from pride. This model advances theory by contextualizing the social function of pride, and suggests new research directions for emotion regulation, impression management, and the rise and fall in social hierarchies, with implications for newcomers, teamwork, and leadership in today's workplace.